The influence of perceived organizational support on employee engagement of La Oma Cafe & Hotel - Simfoni Permata Mustikasari; Moh Benny Alexandri; Pratami Wulan Tresna (Universitas Nusa Cendana, 2026)
This study examines the extent to which perceived organizational support shapes employee engagement within the hospitality sector, drawing on a case study conducted at La Oma Café & Hotel. A descriptive-causal quantitative research design was utilised to explore the nature of the association between organisational support and workforce engagement. Data collection involved all employees through a saturated sampling approach, employing structured questionnaires alongside semi-structured interviews, with the data subsequently subjected to simple linear regression analysis. The results demonstrate that perceived organizational support exerts a positive and statistically significant influence on employee engagement, suggesting that employees who hold stronger perceptions of organisational care, recognition, and backing are more disposed to exhibit elevated levels of dedication, commitment, and active involvement in their professional responsibilities. These outcomes affirm the strategic value of establishing a nurturing organisational climate as a mechanism for enhancing workforce engagement, particularly in hospitality enterprises where the quality of human capital bears directly on service excellence and overall organisational effectiveness. This study advances the fields of organisational behaviour and hospitality management by contributing empirical insights into the function of perceived organizational support in fostering employee engagement, while offering actionable guidance for practitioners and managers aiming to strengthen workforce commitment through the implementation of supportive human resource practices. Keywords: Perceived Organizational Support; Hospitality Industry; Employee Engagement